Mechanical and Wear Performance Evaluation of Natural Fiber/Epoxy Matrix Composites - Sivasubramanian Palanisamy; Sumesh Keerthiveetil Ramakrishnan; Carlo Santulli; Tabrej Khan; Omar Shabbir Ahmed (BioResources, 2024)
Fibers collected from the husk of areca nut trees were chopped to a length of 30 mm and were either used as such or subjected to alkaline treatment by immersion in a 5% sodium hydroxide (NaOH) solution. The untreated and treated fibers were investigated using thermogravimetric analysis (TGA) before the fabrication of composites using an epoxy matrix. Different amounts of fibers were introduced in the matrix, fabricating the composite by compression molding. The composites were subjected to tensile, flexural, and Charpy impact and Shore D hardness testing, which all demonstrated the considerable advantage obtained with the growing quantity of fibers, especially when employing treated fibers, except in the case of hardness, where limited advantages were encountered. Wear tests were carried out on treated fiber composites and the surface morphology of the worn-out samples was studied, which also demonstrated the improvement in fiber-matrix bonding obtained with the growing amount of fibers. The main limitation of the fibers was their low elongation even after treatment. The fibers hardly reached 4%, which might represent a quite normal value for this kind of fibers, possibly due to with tendency to fibrillation. This would somehow compare these composites with others with similar amounts and lengths of natural fibers.